KEANEKARAGAMAN ASPERGILLUS PADA BERBAGAI TRADISIONAL SIMPLISIA JAMU - Rukmi, Isworo (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT—The presence of Aspergillas sp. in the simplisia commonly consumed by Javanese people as a traditional medicine has been done. The eight simplisia examined were: kunyit rhizome (Cucurma domesfica Val.), temuireng rhizome (Cucurma aeroginosae), daun sambiloto (Andrographis paniculata), temulawak rhizome (Cucurma xanthorhizu), and mahkota dewa (Phaleria macrocarpa). Sixteen Aspergillus species were found from the samples, came from the niger, flavus, versicolor, wentii, fumigatus, ochraceus dan ornatus group. Isolates found in this study were A. parositicus, A. flavas, A. oryzae, A. tamarin, A. clavato-flavus, A. flavofurcatis, A. tubingiensis, A. awamori, A. ochraceus, A. sulphureus, A. melleus, A. ornatus, A. brunneo-uniseriatus, A. versicolor, A. wentii, and A. fumigatus, the first six are the member of flavus group that found in all simplisia samples. Nine species of the isolatesknown as mycotoxin producers.Keywords : Aspergillus, simplisia, mikotoksin